Effect of wear parameters on dry abrasive wear of RZ5-TiC in situ composite. Issue 2 (12th March 2018) - Mehra, Deepak; Mahapatra, Manas Mohan; Harsha, Suraj Prakash
Abstract : Purpose: The purpose of this study is to increase the wear resistance of Mg alloy by adding hard ceramic particles to it. The inclusion of hard ceramic particles further strengthen the Mg alloy, resulting in higher wear resistance. Mg alloys containing Zn, rare earth and Zr exhibit high specific strength and excellent creep resistance, making them suitable for aerospace components such as aircraft gearboxes and generator housings. Design/methodology/approach: In the present study, composites have been produced in situ by using RZ5 mg alloy as matrix and TiC as reinforcement by self-propagating high-temperature synthesis technique. The abrasive wear behavior of RZ5 Mg alloy matrix reinforced with TiC particulates has also been examined. The pin-on-disc apparatus has been used for the tests. The abrasive paper is used as a counter body, and the results are obtained by changing sliding distance and applied load. Findings: A notable enhancement in the wear resistance and mechanical properties of tested composite has been observed as compared to the RZ5 Mg alloy as a matrix. There is a uniform increment in the change in weight loss of RZ5-TiC composite with increasing sliding distance and applied load, but it decreases with increasing TiC content. The coefficient of friction (µ) also decreases uniformly with an increase in the reinforcement of TiC, but it decreases with an increase in applied load and sliding distance. The investigation of the worn composite, which determines dominant wear mechanisms as abrasion and plowing grooves on tested samples, has been done using field emission scanning electron microscopy. Originality/value: The current manuscript provides a detailed abrasive wear analysis of RZ5-TiC composite by using different wear parameters. Specifically, extensive experimental data have been provided for RZ5-TiC composite. The effects of parameters such as applied load, sliding distance and Wt.% of TiC on the weight loss and coefficient of friction of the composites have been analyzed and discussed thoroughly.